Non-AIDS–Defining Cancers in New Orleans. (May 2013) - Ruiz, Marco; Johnson, Daniel; Reske, Tom; Cefalu, Charles; Estrada, John
Background: Non-AIDS–defining cancers in HIV-infected patients in the highly active antiretroviral therapy era have increased. To our knowledge a comprehensive review of non-AIDS–related malignancies in New Orleans has not yet been conducted. Methods: Databases from main institutions in New Orleans were queried retrospectively for the years 2001 to 2011. The International Classification of Diseases, Ninth Revision codes were used to search for HIV infection and cancer comorbidity. Results: A total of 16 patients were diagnosed with lung cancer (mean age 50 years) with 81% of the patients presenting with advanced stages. In all, 20 (mean age 47 years) were diagnosed with anal cancer, and 35% presented in late stages. In all, 14 patients (mean age 42 years) were diagnosed with Hodgkin Lymphoma, and 64% were diagnosed at late stage. A total of 5 women (mean age 44 years) were diagnosed with breast cancer with 40% of them presenting at late stage. Conclusion: Malignancies were diagnosed at late stages in the majority of the cases, presented with worse outcomes, and had higher recurrence rates. The role of HIV and other viruses (Epstein Barr virus, human papillomavirus) and the potential mechanisms or pathways of oncogene activation also need to be clarified.